The Exchange of Documents between the Fund and Regional Financing Arrangements. (Policy Papers; Policy Paper ;, 2018)
The changing contours of the global economy and the rapid transformation of the global financial safety net (GFSN) have strengthened the case for more structured collaboration between its different layers, particularly with Regional Financing Arrangements (RFAs). RFAs have become an important part of the GFSN, and their roles have also evolved. Over recent years, their coverage has expanded to encompass many major advanced and emerging market economies; the resources under their control has risen. Moreover, since the global financial crisis, some RFAs have become key financing counterparts of Fund-supported programs. These developments have heightened the importance of close and timely collaboration with RFAs. However, there is currently no formal framework for an exchange of Board documents with RFAs, leaving a gap in Fund collaboration with RFAs. The Fund has a long-standing practice for collaborating and sharing documents with other international organizations, primarily under the Transmittal Policy that was amended most recently in November 2017. However, some RFAs do not meet the criteria under the Transmittal Policy and, in view of the unique and heterogeneous institutional and governance structures of RFAs, there is a need for a dedicated and coherent framework that facilitates the exchange of documents on both routine and non-routine bases. This paper proposes a policy framework for the exchange of documents between the Fund and RFAs. The proposed framework establishes a set of criteria to be met by RFAs for document exchange-based on the consideration of whether a certain entity shares common operational interest with the Fund, and provides satisfactory confidentiality and reciprocity assurances. Under routine document sharing arrangements with RFAs, Board documents would be provided after Board consideration. In cases of UFR arrangements involving current or potential co-financing by the Fund and RFAs, or Policy Coordination Instruments (PCIs) and Policy Support Instruments (PSIs) that may help unlock RFA financing to the country, staff proposes that relevant Board documents be exchanged prior to their consideration by the Board, following notification to the Board. The proposed framework builds on the principles of the Transmittal Policy and does not impact the transmittal of documents to international organizations currently governed by the Transmittal Policy.